Challenges of The Urban Squatters in Sentul, Kuala Lumpur: From the eyes of the policymakers / Zulaikha Abdul Patah Hasan and Mahazril 'Aini Yaacob - Abdul Patah Hasan, Zulaikha; Yaacob, Mahazril 'Aini (2021)
Urban squatter refers to a group of people, generally from a more disadvantaged group who could not have proper access to housing and frequently living in inadequate housing structures with a lack of essential services such as poor maintenance, insufficient amenities, overcrowding, and dangerous areas (Economic Planning Unit, 2015; Aldrich, 2016; Kuek, Abdullah & Hamdan, 2016; Abdullah, Kuek, Hamdan & Zulkifli, 2017; Anindito, Maula & Akbar, 2018). The issues of urban squatters have become a global issue including in Malaysia (Dikovic, 2019). For instance, in Kuala Lumpur, the urban squatters have existed due to the low-income group who migrated to find a job to support their family and had a problem finding an affordable house (Aldrich, 2016; Abdullah et al. 2017; Kuek et al., 2016). As such, for those who could not afford to house, it forces people to seek another alternative housing solution by settling in squatter houses (Dikovic, 2019). Goal 11 of the Sustainable Development Goals (SDG) highlighted that the authorities must take serious action in progressing towards access for adequate, safe, and affordable houses with essential services to all populations, especially the urban squatters (United Nations Development Program (UNDP), 2018). If there is no significant transformation in the way of build and manage urban spaces, goal 11 of Sustainable Development Goals (SDG) cannot be achieved because the population in urban areas will rise to 6.5 billion people by 2050 which might affect the humans and development of the cities (UNDP, 2020).